Radio Resource Allocation in D2D Underlay Communication Using Two Phased Auction Based Fair and Interference Resource Allocation - Alfiya Syifana; Linda Meylani; Vinsensius Sigit Widhi Prabowo (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
The high demands of the mobile user will affect the workload of eNodeB, which results in the decreasingperformance system of eNodeB. Device-to-Device (D2D) underlaying communication system is a solution inreducing the workload of eNodeB and increasing the system data rate. This communication system consistsof two users, namely Cellular User Equipment (CUE) and D2D pair, where CUE shares its resources withthe D2D pair. This sharing of resources also causes interference and should be managed using the resourceallocation algorithm. This research used the TAFIRA D2D algorithm and compared it with the greedyalgorithm and the TAFIRA CUE algorithm. The research calculates parameter performance of the system,such as spectral efficiency, power efficiency, and fairness among D2D pairs. The simulation results showthat Greedy algorithm has a better performance compared with TAFIRA algorithm. TAFIRA D2D onlycan achieve 19.94 bps/Hz in spectral efficiency, 23.88 Kbps/watt in power efficiency, and 89% fairnessamong D2D pairs.